Numerical testing in analyzing the performance of gas turbine models - Jothi Bash Kheerthi Vasan (2013)
Numerical testing of gas turbines is one of the major tasks in a gas turbine design and manufacturing industry which is used to analyze the performance of the engines developed by the manufacturer. Significance of the testing involves assessing the operational behavior of the engine which helps in the targeting the engines to the potential markets available in the world.